2011
DOI: 10.1007/s00439-011-0970-4
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay

Abstract: The proximal long arm of chromosome 15 has segmental duplications located at breakpoints BP1-BP5 that mediate the generation of NAHR-related microdeletions and microduplications. The classical Prader-Willi/Angelman syndrome deletion is flanked by either of the proximal BP1 or BP2 breakpoints and the distal BP3 breakpoint. The larger Type I deletions are flanked by BP1 and BP3 in both Prader-Willi and Angelman syndrome subjects. Those with this deletion are reported to have a more severe phenotype than individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(221 citation statements)
references
References 47 publications
9
206
3
1
Order By: Relevance
“…The 15q11.2(BP1-BP2) deletion has previously been shown to confer modest risk of schizophrenia 1 , behavioural disturbances 17 , developmental and language delay 18 , and epilepsy 19 . We show that the 15q11.2(BP1-BP2) deletion has only modest impact on results of the neuropsychological tests but is still strongly associated with a history of difficulties in learning mathematics and reading (Fig.…”
Section: Lm I Andmentioning
confidence: 99%
“…The 15q11.2(BP1-BP2) deletion has previously been shown to confer modest risk of schizophrenia 1 , behavioural disturbances 17 , developmental and language delay 18 , and epilepsy 19 . We show that the 15q11.2(BP1-BP2) deletion has only modest impact on results of the neuropsychological tests but is still strongly associated with a history of difficulties in learning mathematics and reading (Fig.…”
Section: Lm I Andmentioning
confidence: 99%
“…Such family analysis highlights the difficulty of predicting the recurrence risk of del15q11.2. Second alterations were also found in 25% (17/69) of del15q11.2 patients by Burnside et al In one of the patients the second CNV was confirmed de novo [Burnside et al, 2011]. In the study of Girirajan et al [2012] the del15q11.2 was the most likely genomic disorder where additional large variants occurred in affected children in comparison to controls (P ¼ 0.00093).…”
Section: Clinical Reports and Association Studiesmentioning
confidence: 79%
“…Only 32% of patients presented with ASD and 29% of patients with ID. In the series of Burnside et al the most common feature in del15q11.2 patients was delayed speech [Burnside et al, 2011].…”
Section: Clinical Reports and Association Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Maternally inherited 15q11-13 duplication is a well described cause of neurodevelopmental phenotypes similar to those in our family, including developmental, speech and motor delays, autism or ASD, seizures, ADD/ADHD, ODD, self-injury and tantrums. 4,9 Only one case of an individual with a neurodevelopmental disorder involving the GABA A cluster on 6q15 (GABRR1 and GABRR) has been reported. 10 This 22-year-old female had intellectual disability, ataxia and severe speech deficiency, with an inversion and a deletion described as 46,XX, del(6)(q13q15),inv(6)(p11.2q15 46,XX, del(6)(q13q15),inv(6)(p11.2q15).…”
Section: Discussionmentioning
confidence: 99%